Stereotactic body radiotherapy for liver metastases. - Aitken, K; Hawkins, M (Elsevier, 2015)
The role for local ablative therapies in the management paradigm of oligometastatic liver disease is increasing. The evidence base supporting the use of stereotactic body radiotherapy for liver metastases has expanded rapidly over the past decade, showing high rates of local control with low associated toxicity. This review summarises the evidence base to date, discussing optimal patient selection, challenges involved with treatment delivery and optimal dose and fractionation. The reported toxicity associated with liver stereotactic body radiotherapy is presented, together with possible pitfalls in interpreting the response to treatment using standard imaging modalities. Finally, potential avenues for future research in this area are highlighted.